Dynamics of internal resettlement during civil war: Evidence from Catalonia (1936–39). (March 2018) - Balcells, Laia
This article explores the dynamics of internal resettlement in times of civil war by using a novel dataset of all municipalities of Catalonia during the Spanish Civil War (1936–39), which includes information on the total number of internally displaced from other parts of Spain that sought refuge in Catalan localities during the civil war. The dataset, which also incorporates information on relevant covariates, is built with a combination of primary (i.e. archival) and secondary sources. The results of the multivariate analyses indicate that political identities have a significant impact on resettlement: people tend to relocate to places where they can find others who share their political and/or ethnic identity; we see this reflected in political and ethnic alignments at the municipal level. In addition, the article uncovers a relevant dynamic in the diffusion of violence at the local level: the arrival of internal refugees in a new locality may have the unintended effect of increasing levels of direct violence due to its role in disseminating credible news of atrocities committed by the other side. The implications of this study go beyond the Spanish case and make a contribution to unpacking dynamics of violence and internal displacement in civil wars. The article also sheds light on some of the mechanisms by which refugee flows can play a role in the diffusion of violence throughout a given country.